Meningkatkan Loyalitas Bidan Melalui Pemasaran Internal di Fasilitas Kesehatan Dasar - Desi Fani Rahmawaty; Nyoman Anita Damayanti; Ernawaty Ernawaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to analyze the relationship between the characteristics of midwives and internal marketing efforts (empowerment, reward system, and capacity building) with midwife loyalty. This research is an analytical study with a population of midwives involved in PONED services at Puskesmas. The results showed that employment status has a positive correlation with loyalty (sig = 0.019). Empowerment efforts and reward systems have no relationship with midwife loyalty, while efforts to increase competence have a positive relationship with commitment (sig = 0.037). In conclusion, the certainty of employment status and the better the efforts to increase competence carried out by the Puskesmas will determine midwives' loyalty in PONED services. Keywords: Midwives, Loyalty, Internal Marketing, PONED